Tinjauan Hukum Islam terhadap Bisnis Affiliate Marketing Amazon - Irfan Ansori, Irfan, M. Muhtarom, S.H., M.H, Dr. M. Muinudinillah Basri, M.A (2015)
The presence of online stores becoming an increasingly attractive alternative to public spending. The online store provides various needs of society, including daily necessities, electronic equipment, to sports equipment. All transactions are conducted with based e-commerce. Amazon is an online shop e-commerce based on the first and the largest in the world, through the amazon.com domain. Since 2008, Amazon launch affiliate program to provide an opportunity for the community of Internet users, selling Amazon products that earn wages or commission from the sale. This study aims to determine the position of contract law and the Amazon affiliate marketing business in a review of Islamic law, as well as covering the mechanism of action, application, as well as the method of payment. This study was based on library research, which studied the mechanism of the contract and the agreement made between the Amazon and the affiliate marketer. After the data collected then used qualitative analysis, which compiled the data for analysis and interpretation. Results from this study provide a conclusion, that Amazon's affiliate marketing program is not contrary to the principles of the Islamic muamalah. Amazon affiliate marketing including the discussion ujrah (wages) in Islam, the contract ju'ālah categories, namely mechanism of wages based on job success. Consideration is also the cause of this contract does not include the Ijarah. As for the mechanism of action, application, as well as the mode of payment is not contrary to the principles of Islam, because the goods sold do not contain elements that conflict with Personality 'and the working mechanism and mode of payment does not contain elements that can cancel the contract. As a suggestion, the Amazon affiliate program can be developed by Muslims as a profitable business model and provide extensive benefits for others. Keywords: Ju'ālah, Affiliate Marketing, Ujrah.